Exploring Company’s Activities in the Field of CSR: The Case of Starbucks - Gozdan, Edyta; Sudolska, Agata (Journal of Corporate Responsibility and Leadership, 2021)
Abstract: Recently CSR has gained companies’ attention due to its strategic importance. In the contemporary economy, the enterprises, especially those that are global corporations, are highly involved in several activities focused on meeting both societal and environmental needs. As caring about the better future for next generations, the companies implementing CSR aim at compensating the side effects related their operations. On the other hand, they aim at building their brands perceived as supporting local communities and engaging in particular environmental projects. One of such global corporations highly involved in CSR field is Starbucks. The aim of the study is to is to explore Starbucks’ activities in the field of CSR. The research process is driven by the three following research questions: (1) What are the main areas of Starbucks’ involvement in CSR activities? (2) What are the main Starbucks’ company objectives in the field of CSR? (3) How does Starbucks implement CSR activities following TBL concept? The exploratory single case study analysis of Starbucks company is applied to answer research questions and achieve the aim of the study. The research results presented in the paper indicate that Starbucks carries out several activities focused on supporting different communities as well as prove that the company is engaged in various projects dedicated to environment protection and climate change resistance.